2016
DOI: 10.1080/23294515.2016.1186757
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing initiatives for institutional review board (IRB) quality improvement

Abstract: Background: Institutional Review Boards (IRBs) have been criticized for inconsistency, delay,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Timely review of protocols was the issue identified as requiring most attention, an issue repeatedly identified in a range of research areas internationally [ 10 , 19 , 22 , 30 ] including disaster research where timeliness is of central importance [ 31 ]. Timely reviews are not simply a matter of inconvenience for researchers; they create significant delays in accessing findings that are of potential great public benefit [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely review of protocols was the issue identified as requiring most attention, an issue repeatedly identified in a range of research areas internationally [ 10 , 19 , 22 , 30 ] including disaster research where timeliness is of central importance [ 31 ]. Timely reviews are not simply a matter of inconvenience for researchers; they create significant delays in accessing findings that are of potential great public benefit [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An initial study of 886 US biomedical and social behavioral scientists [ 19 ] generated a baseline ‘US National Validation Sample’ (USNV Sample) to validate the IRB-RAT. Subsequent studies have used the IRB-RAT to capture the perceptions of medical researchers at specific institutions [ 20 , 21 ] and to guide quality improvement of IRB functioning by identifying the areas in which perceived actual IRB processes particularly fall short of the identified ideal processes [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to explore the how IRB stakeholders' perceptions of IRB performance and culture correlate with total review times, we merged this dataset with the results from an associated survey of IRB members' and investigators involved with the protocols studied here [23]. We found no correlation between review time and the survey responses from investigators.…”
Section: Association With Perceptions Of Irb Performancementioning
confidence: 94%
“…Several investigations have analyzed the inconsistencies in IRB panels' results [10][11][12][13][14]. In addition, consistent IRB results are associated with quality of IRB discussions and determinations based on appropriate attention to important issues and ful lling the expectation of researchers [15,16]. However, due to the characteristics of the IRB and its reviews, including its diverse members and complex study designs, inconsistencies are inevitable.…”
Section: Introductionmentioning
confidence: 99%